Downward nominal wage rigidity in Canada: Evidence against a "greasing effect" - Joel Wagner (Bank of Canada, 2017)
The existence of downward nominal wage rigidity (DNWR) has often been used to justify a positive inflation target. It is traditionally assumed that positive inflation could "grease the wheels" of the labour market by putting downward pressure on real wages, easing labour market adjustments during a recession. A rise in the inflation target would attenuate the long-run level of unemployment and hasten economic recovery after an adverse shock. Following Daly and Hobijn (2014), we re-examine these issues in a model that accounts for precautionary motives in wage-setting behaviour. We confirm that DNWR generates a long-run negative relation between inflation and unemployment, in line with previous contributions to the literature. However, we also find that the increase in the number of people bound by DNWR following a negative demand shock rises with inflation, offsetting the beneficial effects of a higher inflation target. As an implication, contrary to previous contributions that neglected precautionary behaviour, the speed at which unemployment returns to pre-crisis levels during recessions is relatively unaffected by variations in the inflation target.
Keywords: E24; E52; 330; Inflation targets; Labour markets